Psikologi Organisasi dan Aspek Kejiwaan dalam Belajar Mengajar dalam Perspektif Hadits - Yunita, Arinda; Ramadhan, Raffly Gilang (BISMA : Business and Management Journal, 2024)
Organizational psychology and psychological aspects in the teaching and learning process play a crucial role in creating a productive and effective environment, both in organizational and educational contexts. Organizational psychology focuses on individual behavior within organizations and how interactions among individuals affect collective performance. In the world of education, psychological aspects are used to evaluate important characteristics such as intelligence, personality, interests, and academic achievements. This research explores the relationship between organizational psychology principles and spirituality from the perspective of the hadith of Prophet Muhammad ﷺ. The first hadith reveals about motivation in an organization, where someone can participate out of fear or love, while the second hadith emphasizes the importance of choosing the right time and conditions in the learning process to avoid boredom. This research aims to explore how the hadith perspective related to organizational psychology and spirituality can be applied to improve quality and effectiveness in organizations and education. Using a qualitative approach and literature study methods, this research analyzes hadith texts and relevant literature in organizational psychology and education. Data is analyzed through a content and interpretative approach to explore the relevance of psychological principles in this context. The research results are expected to provide new insights into the application of organizational psychology and mental health in improving learning effectiveness and performance in educational organizations